Rancang Bangun Pemutus Otomatis Charger Baterai Laptop dengan Algoritma Watchdog Berbasis Single Board Microcontroller - Adlan Bagus Pradana; Bima Wahyu K; Dian Kusuma J; Faisal Zeqlyw H; Thalia Roza Y (PTE FTK UIN Ar-Raniry, 2021)
Laptop is kind of device which recently used by students, teachers, workers, professionals or executives. As the electronics tools, Laptop is supported by a battery and charger. To save battery life, laptop users usually disconnect the charger from the laptop while the indicator shows the battery is fully charged or when the laptop is turned off. However, due to practicality considerations, it often happens that the AC side of the charger is still connected to the voltage source. However, it was a waste condition. Because even though it's small, when the battery is full the charger still dissipates power. In this study, a device was designed and built which has the ability to disconnect the AC source from the charger when the DC charger side is not connected to the laptop. The watchdog algorithm is used to determine when the current should be cut off. The device is realized by using a Single Board Microcontroller (SBM) and a current sensor ACS712.